Curcumin Activates AMPK Pathway and Regulates Lipid Metabolism in Rats Following Prolonged Clozapine Exposure - Liu, Zhen; Cui, Changmeng; Xu, Pengfei; Dang, Ruili; Cai, Hualin; Liao, Dehua; Yang, Mengqi; Feng, Qingyan; Yan, Xin; Jiang, Pei (Frontiers in Neuroscience, 2017)
The atypical antipsychotic, especially clozapine (CLO), is often associated with serious metabolic side effects, such as dyslipidemia, whereas hepatic sterol regulatory element-binding proteins (SREBPs) are central in allosteric control of lipid biosynthetic pathways. Emerging evidence indicates that CLO can activate SREBP pathway and enhance downstream lipogenesis, while curcumin (CUR) contains hypolipidemic properties. Therefore, in this study, we examined the protective effects of CUR against CLO-induced lipid disturbance and analyzed the expression of key components in lipid metabolism. Our data showed that 4-week treatment of CLO (15mg/kg/day) markedly elevated serum lipid levels and resulted in hepatic lipid accumulation, whereas co-treatment of CUR (80mg/kg/day) alleviated the CLO-induced dyslipidemia. We further demonstrated that CUR appears to be a novel AMP-activated protein kinase (AMPK) agonist, which can interact with AMPK in the molecular docking analysis and enhanced AMPK phosphorylation. Additionally, CUR also mitigated the CLO-induced overexpression of SREBP and downstream SREBP-targeted lipogenic genes. In summary, our study suggested that the suppressed AMPK activity and thereby enhanced SREBP-dependent lipid synthesis could be associated with the antipsychotic-stimulated dyslipidemia, whereas CUR may maintain lipid homeostasis by directly binding to AMPK, indicating that adjunctive use of CUR could be a promising preventive strategy for the drug-induced lipogenesis.